Look for me here 299 days in the life of Nora Lenihan - DelSanto, Florence; Melville, Tom; Foreman, Judy ([Newton, Mass.] : New England Cable News, 1997)
(Producer) When she learned that her breast cancer had recurred and metastasized, Nora, then a 40-year-old social worker, chose to forego radical treatment, and to face death with hospice care at home. Focusing on the comfort provided by her caregivers and family, and by an extraordinary extended support network of friends and co-workers, this unfliching video portrait chronicles the year from that decission to her death.
Videocassette is available at Koleksi Media, PHUKM
Keywords: Breast Neoplasmas -- psychology; Hospice Care -- psychology; Attitude to death; Caregivers -- Psychology